Recycling of AlMgSi1 aluminium chips by cold compression - T. Pepelnjak; K. Kuzman; I. Kačmarčik; M. Plančak (Metalurgija, 2012)
Current work elaborates possibilities for direct conversion of AlMgSi1 aluminium chips into solid billets by solid state recycling. Milling chips from an aluminium alloy were cold compressed in a closed cylindrical die by means of a 2,5 MN hydraulic press. Due to low initial relative density of the chips, several pre-compressions were needed. In order to establish the infl uence of chip geometry on the final density of billets different types of chips were cut by using various milling regimes. The infl uence of a compression regime due to various chip types were followed by load–stroke diagrams. Up to 97 % of density measured at extruded aluminium was attained for one type of chips. Results show that the shapes of the chips and their size (especially thickness) have a considerable infl uence on the final integrity of billets.